#QuadrosDiscentes: Research into memes and art in teacher training in Brazil and Spain (Revista Apotheke, 2024)
In this paper we reflect on and present the results of part of a research project we conducted in academic years 2018-2019 and 2019-2020 with students of the Double Degree in Infant and Primary Education of the University of Girona - UdG (Catalonia, Spain) and students of the Degree in Visual Arts of Santa Catarina State University - UDESC (Brazil), concerning Internet memes and their linguistic strategies. In order to bring the two fields of study together and facilitate collaboration, a closed group within the Facebook social network was used as a space of interaction between the research subjects. The researchers took part in the experience, in accordance with the protocols of the action research method. The results point towards reflections and potential modifications that could be introduced in new research into how to learn and teach about volatile images—typical of cyberculture—in educational processes for teacher training.
Keywords: internet memes; liquid languages; teacher training; art education; cyberculture